ANALISIS KINERJA KONTRAK DESIGN AND BUILD DAN PEMILIHAN JENIS KONTRAK TERBAIK UNTUK PROYEK PELABUHAN BERBASIS AH - Agung Hadi Brantas; Henny Pratiwi Adi; Kartono Wibowo (Jurnal Teknik Sipil dan Arsitektur, 2026)
The selection of contract types for port construction projects is a strategic decision that affects the success of project implementation, particularly in managing risks, costs, and technical complexities. This study aims to analyze the performance of Design and Build contracts in port projects and determine the most suitable contract type using the Analytical Hierarchy Process (AHP) method. This study uses a descriptive quantitative approach with case studies on three port projects, namely the Ex. Semen Tonasa Port Branch Banjarmasin Stacking Field Paving Project, the Batang Multipurpose Terminal Phase I Development, and the Design and Build Revetment and Retaining Wall Dumping 1 Benoa Port. Project performance analysis was conducted based on time deviation and profit percentage against the contract BOQ. Furthermore, the best contract type was determined using the AHP method through the preparation of a decision hierarchy, pairwise comparisons between criteria and alternatives, priority weight calculations, and consistency ratio testing. The results of the study show that all projects experienced time extensions of between 25% and 56%, but still generated positive profits with margins of between 8.69% and 22.79%. AHP analysis with four main criteria of risk level, cost, scale of work, and source of financing shows that the risk level has the highest weight of 0.518 (51.8%). The global priority calculation resulted in the Design and Build contract as the most suitable alternative with a weight of 0.49 (49%), followed by the conventional contract (0.27) and Lump Sum (0.24). This study concludes that for port projects with high complexity and risk, the Design and Build contract is the most effective option because it integrates design and construction into one coordinated responsibility.